Squarks Decay into Quarks and Gluinos in the MSSM with Complex Parameters - Bang, Ha Huy; Cuong, Nguyen Chinh; Huong, Nguyen Thi Thu (Communications in Physics, 2012)
We discuss the decay of squarks (stop and sbottom) into quarks (top and bottom) and gluinos in the Minimal Supersymmetric Standard Model (MSSM) with complex parameters A_t, A_b. The analytical and numerical results for the decay widths are given. We show that the effect of these CP phases on the decay widths of stop and sbottom decay can be quite significant in a large region of the MSSM parameter space. SUSY-QCD corrections to the decay widths have been included.